Intellectual freedom manual (American Library Association, 2006)
Libraries, havens for the free exchange of ideas and information, face wide-ranging challenges relating to privacy and censorship from government, special interest groups, and others. With the updated seventh edition of the Intellectual Freedom Manual, librarians have practical support at hand to address these troubling problems. This bible for intellectual freedom includes the most up-to-date intellectual freedom guidelines, policies, and interpretations of the Library Bill of Rights, along with the ALA Code of Ethics and Freedom to Read Statement. Eight newly Amended policies:. Access for Ch.